2021
DOI: 10.1155/2021/6298565
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Behavior of Moxa Floss Using Thermogravimetric and Pyrolysis-GC/MS Analyses

Abstract: Moxa floss is a type of biomass used as the main combustion material in moxibustion, a therapy that applies heat from moxa floss combustion to points or body areas for treatment. Safety concerns regarding moxa smoke have been raised in recent years. Since moxa floss is the source material in moxibustion, its thermal behavior and pyrolysis products would be related to the products formed in moxa smoke. This work aims to understand the thermal behavior of moxa floss and investigate the pyrolysis products generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…[58][59][60][61][62][63] Therefore, our hypothesis is that the efficacy and safety of MS possibly should be affected by the level of MSC, moxa quality and duration of exposure in MS. Firstly, moxa aged more than three years is considered as quality guarantee for its characteristics, and the moxibustion duration usually lasts for 20-30 min for each session. 64 Hence, moxa that has been aged for three years will be utilized in 30-minute treatment sessions in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60][61][62][63] Therefore, our hypothesis is that the efficacy and safety of MS possibly should be affected by the level of MSC, moxa quality and duration of exposure in MS. Firstly, moxa aged more than three years is considered as quality guarantee for its characteristics, and the moxibustion duration usually lasts for 20-30 min for each session. 64 Hence, moxa that has been aged for three years will be utilized in 30-minute treatment sessions in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical trial, moxa floss that has been aged for five years will be utilized, in order to ensure an even higher standard of quality and safety. 31 Few studies have been published that address the ideal duration of exposure to MS. One study found that exposure to moxibustion at a MSC level of 2.5 ± 0.5 mg/m 3 twice in one week, for 25 minutes per session, induced no significant adverse effects on heart rate or heart rate variability in young, healthy adults. 53 A cross-sectional survey of 803 acupuncturists in China who regularly practice moxibustion treatment, using the American Thoracic Society Division of Lung Disease questionnaire (ATS-DLD-78-A), showed that long-term, regular exposure to MS did not appear to have a significant causal relationship with respiratory diseases and symptoms in these practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical experience accumulated by doctors over many centuries in China, it is felt that Folium Artemisiae argyi that has been aged for at least three years is the most suitable material for moxibustion. 31 The mass concentration of particulate matter (PM) generated with an aerodynamic diameter of less than 10 mm (PM 10 ) has been evaluated in some studies in order to quantify MSC and evaluate the degree of air pollution produced during moxibustion. 29 , 32 According to one noteworthy study conducted in Beijing and Tianjin, China, the average PM 10 produced in a typical moxibustion treatment in China, using standard materials in an enclosed room, was observed to be 3.54 mg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin is the medicine for treating malaria. Artemisia argyi , like Artemisia annua , belongs to the genus of composite and is the main material of moxibustion [ 13 ]. The clinical application of moxibustion and MS was recorded in “Handbook of Prescription for Emergency.” The original text was “in order to cut off the spread of pestilence, the moxa floss can be ignited and placed around the patient's bed to eliminate the virus infection.” Since the outbreak of the COVID-19 in 2020, MS has been used to sterilize the air in China and is also reported to have anti-inflammatory effect to regulate autonomic functions [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin is the medicine for treating malaria. Artemisia argyi, like Artemisia annua, belongs to the genus of composite and is the main material of moxibustion [13]. e clinical application of moxibustion and MS was recorded in "Handbook of Prescription for Emergency.…”
Section: Introductionmentioning
confidence: 99%